Texts, tasks, and theories - Klein, Tobias Robert; Auga, Ulrike; Prüschenk, Viola (Matatu, 2007)
African literary theory has recently gained immensely from an emerging multitude of perspectives and scholarly approaches. This volume offers a welcome opportunity to assess trends in the twenty-first century's discourse on African literature: Twelve different articles treat such lively issues as modernity, nation, civil society, postcolonial theory, and feminism, relating these both to more recent short stories, poems, and novels and to a large variety of texts that have in one way or another acquired canonical status. The first section "Language, Modernity and Modernism" explores ocial and a.